Child sexual abuse and its determinants among children in Addis Ababa Ethiopia: Systematic review and meta-analysis. - Birye Dessalegn Mekonnen; Sintayehu Simie Tsega (Public Library of Science (PLoS), 2024)
Child sexual abuse is a significant public health concern and a breach of basic human rights affecting millions of children each year globally. It is typically not reported by victims, hence it remains usually concealed. Except for single studies with varying reports, there is no national studies conducted on child sexual abuse in Ethiopia. Therefore, this review determined the pooled magnitude and determinants of sexual abuse among children in Ethiopia. Potential articles were searched from PubMed, Science Direct, Scopus, and Web of science using relevant searching key terms. The Joanna Briggs Institute (JBI) critical appraisal checklist was used to evaluate the quality of all selected articles. Data were analyzed using STATA Version 14 software. Publication bias was checked using Egger's test and funnel plot. Cochran's chi-squared test and I2 values were used to assess heterogeneity. A random-effects model was applied during meta-analysis. The pooled prevalence of sexual abuse among 5,979 children in Ethiopia was 41.15% (95% CI: 24.44, 57.86). Sex of children (OR: 2.14, 95%CI: 1.12, 4.06), smoking (OR: 4.48, 95%CI: 1.26, 76.79), khat chewing (OR: 3.68, 95%CI: 1.62, 21.93), and alcohol use (OR: 4.77, 95%CI: 2.22, 10.25) were the determinants of child sexual abuse. The main perpetrators of sexual abuse against children were neighbors, boy/girlfriends, family members, school teachers, and stranger person. Child sexual abuse commonly took place in the victim's or perpetrator's home, school, and neighbor's home. This review revealed that the magnitude of child sexual abuse in Ethiopia was relatively high and multiple factors determined the likelihood of sexual violence against children. Thus, policy-makers and concerned stakeholders should strengthen comprehensive sexual and reproductive health education to reduce the magnitude and consequences of child sexual abuse. Moreover, support with special attention should be given to children with mental illness and physical disabilities.